(1606) جدوى بناء أطر ونماذج للمشروعات الصناعية الصغيرة لتعميق فكر العمل الحر فى جمهورية مصر العربية. The feasibility of building frameworks and models for small industrial projects to deepen the concept of self-employment in the Arab Republic of Egypt. - الشربيني، إيمان أحمد. (معهد التخطيط القومي, 2018)
يناير 2001.